Metal-Organic Frameworks With Variable Valence Metal-Photoactive Components: Emerging Platform for Volatile Organic Compounds Photocatalytic Degradation - Qian, Yuhang; Ma, Dongge; Zhong, Junbo (Frontiers in Chemistry, 2021)
With their outstanding diversities in both structures and performances, newly emerging metal-organic frameworks (MOFs) materials are considered to be the most promising artificial catalysts to meet multiple challenges in the fields of energy and environment. Especially in absorption and conversion of solar energy, a variety of MOFs can be readily designed to cover and harvest the sun irradiation of ultraviolet (UV), visible and near-infrared region through tuning both organic linkers and metal nodes to create optimal photocatalytic efficiency. Nowadays, a variety of MOFs were successfully synthesized as powerful photocatalysts for important redox reactions such as water-splitting, CO2 reduction and aqueous environmental pollutants detoxification. MOFs applications in indoor-air VOCs pollutants cleaning, however, are less concerned partially because of limited diffusion of both gaseous pollutant molecules and photo-induced active species in very porous MOFs structures. In this mini-review, we focus on the major breakthroughs of MOFs as photocatalysts for the effective removal of indoor-air VOCs such as aldehydes, aromatics and short-chain alcohols. According to their nature of photoactive centers, herein MOFs photocatalysts are divided into two categories to comment, that is, MOFs with variable valence metal nodes as direct photoactive centers and MOFs with non-variable valence metal nodes but after combining other photoactive variable valence metal centers as excellent concentrated and concerted electron-transfer materials. The mechanisms and current challenges of the photocatalytic degradation of indoor-air VOC pollutants by these MOFs will be discussed as deeply as possible.